An Analysis of Grammatical Errors in Writing Abstract of Skripsi Made by English Language Education Students at University of Islam Malang - Aminah - (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This article aims at knowing what types, what the frequencies, and what are the causes of grammatical errors in writing abstract made by the English language education students at university of Islam Malang. The research design in this study is qualitative research design in the form of descriptive design. The subject of this study is the abstracts of skirpsi made by the English language education students 2017/2018 academic year, and it consists of 30 writing abstracts. There are some types of grammatical errors made by the English language education students at university of Islam Malang, those are omission of article, 35 items (20.23%) of substitution singular to plural, 16 items (9.24%) of disagreement of subject and tenses, 4 item (2.31%) of substitution singular to plural, 1 item (0.67%) of omission of to be, and 1 item (0.57%) of omission of main verb. The causes of the grammatical made by students were interlingual transfer, limited knowledge of English grammar, and carelessness. Key words: Grammatical Errors, Abstracts, Skripsi